NITROGEN SOURCE EFFECT ON COPPER SPECIATION WITHIN ECTOMYCORRHIZAL FUNGUS RHIZOPOGON RUBESCENS - М. О. Фомiна (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
Aim. The aim of this work was to study the effects of nitrogen source on the speciation of copper accumulated by fungi and ectomycorrhizas grown in the presence of copper phosphate. Materials and Methods. Ectomycorrhizal fungus Rhizopogon rubescens and its symbiotic ectomycorrhizal association with Scots Pine were grown in the presence of copper phosphate at different nitrogen sources: either ammonium or nitrate. The coordination of copper released from copper phosphate and bioaccumulated by fungus and ectomycorrhiza was determined by using synchrotron-based X-ray absorption spectroscopy (XAS). Results. XAS data showed that the change of nitrogen source from ammonium to nitrate was shifting copper coordination by mixed oxygen ligands towards oxalate coordination of copper. Conclusions. It was found that the conditions of growth of fungi and mycorrhizas may change the nature of ligands available for sequestering toxic metals and coordination of copper within ectomycorrhizal fungus R. rubescens and its symbiotic association with pine roots depended on nitrogen source.